Monitoring of surface instability in tourist zones in Sanya (China) using high-resolution SAR interferometry. Issue 2 (1st February 2019) - Tang, Panpan; Chen, Fulong; Tian, Bangsen; Zhang, Hailong; Miao, Zhao; Wang, Qinjun; Zhou, Wei
ABSTRACT: Sanya City, in China, is experiencing rapid urbanization and expansion of tourism, followed by various geological hazards. In this letter, 25 spotlight-mode TerraSAR-X images (acquired from March 2010 to November 2011) and Multi-temporal spaceborne Synthetic Aperture Radar (SAR) interferometry were used for the wide-area instability monitoring of a tourist zone in Sanya, China. The Persistent Scatterers (PSs) were first extracted in the settlement region, and then the Distributed Scatterers (DSs) were identified in the suburban and mountain regions to increase the monitoring extent; this was followed by a temporal-spatial filtering to reduce the decorrelation noise. The Small BAseline Subset (SBAS) method was used for the deformation estimation and instability mapping. The results show that several mountain slopes and urban grounds were unstable and subsiding, and potential security risks existed. The main reasons were human activities such as construction, forest harvesting, farming, mining, and even tourism. The findings highlight the effectiveness of PS-DS integrated multi-temporal interferometry in the coastal city and facilitate the hazard prevention, tourism planning and management decisions.